THE ASSOCIATION BETWEEN STRESS AND SMOKING HABITS AMONG PRISONERS AT THE SURABAYA CORRECTIONAL INSTITUTION - Cempaka, Anindya Arum; Lilyana, Maria Theresia Arie (Quality : Jurnal Kesehatan, 2025)
Background: Imprisonment is a big part of the stressor. People who initially live freely are stripped of their independence and freedom in a prison or detention center. They are always monitored and restricted in their movements and behavior. In addition, they cannot interact with their family, have to live in prison with strict supervision, and need some adjustments to live a new life. Everyone has different ways of coping with stress; some take a positive way while others take a negative one, such as smoking. Methods: This study uses a correlation design with a cross-sectional approach. This research was carried out in December 2022 at the Surabaya Correctional Institution, involving 35 male adult respondents. A modified questionnaire was used as the instrument to obtain information about the independent variable, i.e., smoking. Meanwhile, the Perceived Stress Scale questionnaire sheet was used as the instrument to find out about the dependent variable, i.e., the level of stress. The bivariate analysis used the Spearman rank test with a significance level of 95% (?=0.05) using SPSS 17. Result: The results show a p-value ?0.05, indicating a relationship between stress and smoking among prisoners. Officers and prisoners who live and are serving criminal sentences are expected to be aware of stress and its causes. Therefore, they can appropriately manage stress to reduce and divert it positively and harmlessly.